Studies on immunoreceptor activation and SARS-CoV-2 RBD/ACE2 interactions - Barton, MI (2022)
The immune system must maintain a very fine balance recognising threats without damaging healthy cells and it uses cell surface non-catalytic tyrosine phosphorylated receptors (NTRs) to achieve this. In order to study this complex behaviour this work has taken a reductionist approach, using artificial systems in order to control as many variables as possible. The use of a generic cell surface ligand system to activate NTRs has suggested that they share a common mechanism for activation and shed light on specific characteristics of this mechanism. While NTRs are significantly different in terms of sequence homology they share similar structural characteristics which make them sensitive to receptor ligand dimensions. I was also able to show that altering the valency of the ligand could improve activation, but this was not due to clustering of the receptor. The mobility of the ligand was shown not to influence activation. Finally, changing the affinity of the ligand suggests the presence of a kinetic proofreading step during receptor activation.